Behavioural and psychological patterns of patients with idiopathic pulmonary fibrosis: a prospective study - Anouk Delameillieure; Fabienne Dobbels; Steffen Fieuws; Katleen Leceuvre; Sara Vanderauwera; Wim A. Wuyts (Respiratory Research, 2022)
Abstract Background Idiopathic pulmonary fibrosis (IPF) is a chronic and progressive lung condition. Currently, care models predominantly focus on acute medical and pharmacological needs. As a step towards holistic care, the aim of this prospective study was to investigate the psychological and behavioural needs of IPF patients treated with pirfenidone from diagnosis until two years of follow-up. Methods The following variables were selected from the literature on patients’ needs and the COM-B model, a theoretical model explaining behaviour: medication adherence, barriers to adherence, importance and intentions of medication adherence, anxiety, depression, health literacy, knowledge, reported side effects, adherence to sun protection recommendations, alcohol use, physical activity, quality of life and health status. Linear and generalised linear models for longitudinal data were used to evaluate the evolution since treatment initiation. Results We included 66 outpatients: 72.7% men, mean age of 70.3 years (range 50–87), predicted mean forced vital capacity of 85.8% (SD 17.4) and predicted mean diffusing capacity for monoxide of 56.9% (SD 15.7). The participants placed considerable importance on following the treatment recommendations. We noticed difficulties regarding health literacy, alcohol use, pirfenidone adherence (decline over time) and adherence to sun protection recommendations (early in follow-up care). There were low levels of physical activity (no effect of time), high body mass indices (decline over time) and moderate levels of depression and anxiety. Conclusion When providing care to IPF patients, behavioural issues, health literacy and psychological well-being should be taken into consideration. There is a need to further explore interventions and care models to tackle these difficulties. Trial registration This study was registered in the ClinicalTrials.gov database (identifier NCT03567785) on May 9th, 2018